Peripheral Muscle Weakness in Patients with Chronic Obstructive Pulmonary Disease - BERNARD, SARAH; LeBLANC, PIERRE; WHITTOM, FRANÇOIS; CARRIER, GUY; JOBIN, JEAN; BELLEAU, ROGER; MALTAIS, FRANÇOIS (American journal of respiratory and critical care medicine, 1998)
Peripheral muscle weakness is commonly found in patients with chronic obstructive pulmonary disease (COPD) and may play a role in reducing exercise capacity. The purposes of this study were to evaluate, in patients with COPD: (1) the relationship between muscle strength and cross-sectional area (CSA), (2) the distribution of peripheral muscle weakness, and (3) the relationship between muscle strength and the severity of lung disease. Thirty-four patients with COPD and 16 normal subjects of similar age and body mass index were evaluated. Compared with normal subjects, the strength of three muscle groups (p < 0.05) and the right thigh muscle CSA, evaluated by computed tomography (83.4 +/- 16.4 versus 109.6 +/- 15.6 cm2, p < 0.0001), were reduced in COPD. The quadriceps strength/thigh muscle CSA ratio was similar for the two groups. The reduction in quadriceps strength was proportionally greater than that of the shoulder girdle muscles (p < 0.05). Similar observations were made whether or not patients had been exposed to systemic corticosteroids in the 6-mo period preceding the study, although there was a tendency for the quadriceps strength/thigh muscle CSA ratio to be lower in patients who had received corticosteroids. In COPD, quadriceps strength and muscle CSA correlated positively with the FEV1 expressed in percentage of predicted value (r = 0.55 and r = 0. 66, respectively, p < 0.0005). In summary, the strength/muscle cross-sectional area ratio was not different between the two groups, suggesting that weakness in COPD is due to muscle atrophy. In COPD, the distribution of peripheral muscle weakness and the correlation between quadriceps strength and the degree of airflow obstruction suggests that chronic inactivity and muscle deconditioning are important factors in the loss in muscle mass and strength.